2005
DOI: 10.1253/circj.69.621
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Free Wall Rupture in Transient Left Ventricular Apical Ballooning

Abstract: ransient left ventricular apical ballooning [1][2][3][4][5][6] in patients with normal coronary angiography results is characterized by transient left ventricular (LV) dysfunction and chest symptoms, together with electrocardiographic (ECG) changes that mimic those of acute myocardial infarction (AMI). Generally, the prognosis for transient LV apical ballooning is good, because in most patients ventricular function improves with conservative therapy. Nevertheless a very small number die from cardiogenic shock.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 10 publications
3
33
1
2
Order By: Relevance
“…Cardiac rupture is the most severe and oftentimes fatal complication of TTC, which supports the transmyocardial damage [28,29]. Histopathological findings at the rupture site include myocardial necrosis with hemorrhaging, fused foci of coagulation necrosis and contraction band necrosis, as well as diffuse patchy infarction of myocardial in the surrounding tear area [30][31][32][33]. In myocardial biopsies, intestinal fibrosis, contraction band necrosis and mild cell infiltration have been described [13,32].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Cardiac rupture is the most severe and oftentimes fatal complication of TTC, which supports the transmyocardial damage [28,29]. Histopathological findings at the rupture site include myocardial necrosis with hemorrhaging, fused foci of coagulation necrosis and contraction band necrosis, as well as diffuse patchy infarction of myocardial in the surrounding tear area [30][31][32][33]. In myocardial biopsies, intestinal fibrosis, contraction band necrosis and mild cell infiltration have been described [13,32].…”
mentioning
confidence: 85%
“…Histopathological findings at the rupture site include myocardial necrosis with hemorrhaging, fused foci of coagulation necrosis and contraction band necrosis, as well as diffuse patchy infarction of myocardial in the surrounding tear area [30][31][32][33]. In myocardial biopsies, intestinal fibrosis, contraction band necrosis and mild cell infiltration have been described [13,32]. Several studies have reported complete recovery of LV systolic function in patients with TTC as analyzed by the LVEF during follow-up [2,34,35].…”
mentioning
confidence: 99%
“…Moreover, few patients were described as asymptomatic, often admitted for non cardiac illnesses, and TTC was suspected on electrocardiogram or cardiac biomarkers. Life-threatening initial symptoms are uncommon and out-hospital cardiac arrest due to cardiac rupture has also been very rarely recorded (Akashi et al, 2004;Ohara et al, 2005). However, hemodynamic compromise may occur, related to acute complications such as ventricular tachycardia, ventricular fibrillation, severe congestive heart failure or left ventricular outflow tract obstruction (Valbusa et al, 2008;Prasad et al, 2008).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…This condition is involved in a large proportion of the syndrome mortality rate, as sudden cardiac death due to ventricular fibrillation was estimated to be 4% (Ionescu et al, 2010). Other rare complications have been noted such as pneumothorax or left ventricular rupture (Bielecka-Dabrowa et al, 2010;Matsuoka et al, 2000;Sakai et al, 2005;Ohara et al, 2005). A TTC complicated by a ventricular septal dissection with a concomitant septal performation have been recently reported (Mariscalco et al, 2010).…”
Section: Complicationsmentioning
confidence: 99%
“…Very rarely, episodes of late sudden death due to cardiac rupture have been recorded. 18,19 A recent 4 year follow-up study of 100 patients reported 11.4% recurrence of transient LV dysfunction and a cardiovascular mortality of 6%; mostly related to arrhythmias. 20…”
Section: Syndrome Presentationmentioning
confidence: 99%